2023
DOI: 10.4018/ijswis.330250
|View full text |Cite
|
Sign up to set email alerts
|

Web Semantic-Based MOOP Algorithm for Facilitating Allocation Problems in the Supply Chain Domain

Chun-Yuan Lin,
Mosiur Rahaman,
Massoud Moslehpour
et al.

Abstract: The facility allocation of the supply chain is critical since it directly influences cost efficiency, customer service, supply chain responsiveness, risk reduction, network optimization, and overall competitiveness. When enterprises deploy their facilities wisely, they may achieve operational excellence, exceed customer expectations, and obtain a competitive advantage in today's volatile business climate. Due to this reason, a multi-objective facility allocation problem is introduced in this research with coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In order to apply the principles and technical knowledge involved in designing and developing software, engineers are equipped with producing scalable complex and sophisticated applications. Cloud computing has been identified as the ideal choice for the development of modern software, since it affords engineers a novel way of developing real-time, cost-effective, and quality software (Lin et al, 2023). Cloud computing is also attractive because it can provide a flexible and resourceful platform for development and deployment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to apply the principles and technical knowledge involved in designing and developing software, engineers are equipped with producing scalable complex and sophisticated applications. Cloud computing has been identified as the ideal choice for the development of modern software, since it affords engineers a novel way of developing real-time, cost-effective, and quality software (Lin et al, 2023). Cloud computing is also attractive because it can provide a flexible and resourceful platform for development and deployment.…”
Section: Related Workmentioning
confidence: 99%
“…Stochastic optimization algorithms are based on adaptive random search methods that require only the objective function and the constraints and not derivatives (Ashok Kumar & Sivakumar, 2022). Many recent stochastic algorithms have been proposed in the literature, such as a duelist algorithm (DA), a genetic algorithm (GA), particle swarm optimization (PSO), and an imperialist competitive algorithm (ICA) (Biyanto et al, 2017;Lin et al, 2023). There are statements that no algorithm is superior to others or the no free lunch theorem (Dhal et al, 2019), and very rare utilization of recent stochastic algorithms is found in the literature on the application of FTCDC design optimization.…”
Section: Introductionmentioning
confidence: 99%